Anterior Talofibular Ligament and Superior Extensor Ankle Retinaculum Thicknesses: Relationship with Balance - Malloy, Brooke; Furrow, David; Cook, Haily; Smoot, Elizabeth; Cash, Lindsey; Aron, Adrian; Jagger, Kristen; Harper, Brent (Journal of Korean Foot and Ankle Society, 2019)
Purpose: This study determined if anterior talofibular ligament (ATFL)/superior extensor ankle retinaculum (SEAR) thicknesses are related to dynamic balance in individuals with chronic ankle instability (CAI). Materials and Methods: The subjects were 14 males and 15 females (age=24.52±3.46 years). Ankle instability was assessed using the Cumberland Ankle Instability Tool (CAIT) with a cut off score of 25 to define two groups. SonoSite MTurbo (Fugifilm Sonosite, Inc.) musculoskeletal ultrasound (MSKUS) unit was used to assess ATFL and SEAR thicknesses. Dynamic balance was measured with the Y Balance Test (YBT) and two NeuroCom balance tests. Results: There were no significant differences in the average ATFL thickness between stable and unstable ankles in those subjects with CAI (0.25±0.03 cm and 0.21±0.05 cm, respectively) or in the SEAR thickness (0.09±0.04 cm and 0.10±0.03 cm, respectively). There were also no significant differences in the right and left ATFL thicknesses (0.23±0.07 cm and 0.21±0.04 cm, respectively) or the SEAR thicknesses (0.09±0.01 cm and 0.09±0.01 cm, respectively) in those without CAI. There were no differences between limbs in composite scores on YBT in those with CAI (p=0.35) and those without CAI (p=0.33). There was a moderate correlation between the left SEAR thickness and the large forward/backward perturbations on the NeuroCom (Natus) motor control test (r=0.51, p=0.006 and r=0.54, p=0.003, respectively). Conclusion: There were no differences in the ATFL/SEAR thicknesses or balance measures between or within the groups, likely because CAI is multi-factorial and related to mechanisms other than tissue changes alone. More sensitive technology and a better definition of the measurement process may provide more definitive results. KCI Citation Count: 0